Environmental regulation, market power and low-carbon development of China's coal power industry chain —Based on both strategy and return perspectives - Jiaming Gao; Li Zhang (Energy Strategy Reviews)
To study the behavioral strategies of government agencies and the coal power industry chain under environmental regulation, an evolutionary game model has been constructed. Furthermore, a reinforcement learning model has been developed using the payoff matrix. By analyzing the characteristics of different environmental regulatory policies and the future development trends of China's coal power industry chain, we evaluate the impact of various regulatory policies on the game players from both strategy and return perspectives. The results show that (1) Power companies are policy sensitive; (2) In the context of both market-based and voluntary environmental regulation policies, there exists a potential to trigger the '' coal-power paradox ''. (3) Market-based environmental regulation is most effective, whereas command-based environmental regulation offers prompt policy feedback, and voluntary environmental regulation merely serve as a supplementary regulatory tool.